Cytotoxicity assay of Typhonium flagelliforme Lodd against breast and cervical cancer cells - Endang Purwaningsih; Etty Widayanti; Yulia Suciati (Faculty of Medicine, Universitas Trisakti, 2014)
BACKGROUNDCancer is one of the causes of high mortality. Breast and cervical cancers are two of the most frequent cancers affecting women around the world, including Indonesia. Natural materials such as rodent tuber (Typhonium flagelliforme) have anticancer potentials. The rodent tuber extract contains ribosome inactivating proteins (RIPs) capable of cutting the DNA or RNA of cancer cells and blocking the growth of cancer cells. The purpose of this study was to evaluate the cytotoxic effects of Typhonium flagelliforme Lodd extract on HeLa cervical cancer and Michigan Cancer Foundation-7 (MCF-7) breast cancer cells.METHODSSubjects were cultured cell lines of HeLa cells in Rosswell Park Memorial Institute (RPMI) and of MCF-7 cells in Dulbecco’s Minimum Essential Medium (DMEM). Rodent tuber ethanolic extract was diluted in dimethyl sulfoxide (DMSO). The cytotoxicity assay used the 3-(4,5-dimethyl thiazol-2-yl,5-diphenyl) tetrazolium bromide (MTT) method. Absorbance was read in an ELISA reader at a wavelength of 595 nm.RESULTSRat tuber extract at all dilutions (500; 250; 125; 62.5; 31.25; 15.625;7.81; 3.9 ì g/ mL) showed cytotoxic effects against HeLa and MCF-7 cells. Higherconcentrations of the extract gave a higher proliferation inhibition effect.Calculated IC50 values of the extract by probit analysis were 30.19 ìg/mL against HeLa cells and 5.586 ì g/mL against MCF-7 cells.CONCLUSIONSEthanolic extract of Typhonium flagelliforme Lodd has cytotoxic effects against HeLa cells and MCF-7 cells. The cytotoxic effects against MCF-7 cells are greater than the cytotoxic effects against HeLa cells.